El cocoliche se devora a sí mismo: Una lectura genealógica del grotesco criollo en Stéfano y La Nona - Aguiar, Gonzalo (Latin American Theatre Review, 2007)
Although much of the criticism on the grotesco criollo has focused on the sociopolitical implications of the plays regarding the assessment of the cocoliche as a symbol of the cultural anxieties at the turn of the past century in the River Plate, little attention has been paid to the intertextual crossings and discursive genealogies within the genre. This article deals with the literary tradition in reference to Armando Discépolo’s Stéfano and Roberto Cossa’s La Nona, but at the same time it proposes a different reading of both texts. First, I suggest that the protagonists of the plays in discussion are discursively intertwined with the theme of the Argentine nation-building as a historical backdrop. Second, and most importantly, the dialogue between these two plays alludes to a retroactive revenge exerted by the matriarchal figure of la Nona against a long period of oppression in which the Italian immigrant witnessed the fall of the liberal dream of everlasting prosperity. (GA, Article in Spanish)